ASXL3 gene variants causing Bainbridge-Ropers syndrome: clinical and genetic analysis of four Chinese patients - Yang, Qi; Zhang, Qiang; Zhou, Xunzhao; Yi, Shang; Qin, Zailong; Yi, Sheng; He, Sheng; Luo, Jingsi (Frontiers in Neuroscience, 2026)
Bainbridge-Ropers syndrome (BRPS, OMIM #615485) is a rare, heterogeneous autosomal dominant genetic disease that is mainly characterized by intellectual disability (ID) of varying degrees, developmental delay (DD), language impairments, failure to thrive, behavioral issues, hypotonia, feeding difficulties, and distinctive craniofacial features. It is caused by heterozygous pathogenic variants in the additional sex combs-like 3 (ASXL3, OMIM #615115) gene. In this study, four Chinese patients were diagnosed with BRPS caused by ASXL3 variants through whole exome sequencing. We detected two novel and two previously reported variants of the ASXL3 gene (NM_030632.3) in these 4 unrelated Chinese patients: two novel variants, namely, c.1276del (p.Val426*) and c.3750del (p.Glu1251Asnfs*5), and two recurrent variants, namely, c.4330C>T (p.Arg1444*) and c.4336_4337delAG (p.Arg1446fs*2). All four patients had a clinical profile similar to that associated with BRPS. Compared with previously reported cases of BRPS, these patients exhibited novel complications, including long eyelashes, congenital laryngeal cartilage hypoplasia and dextrocardia. These findings broaden our understanding of the mutational and clinical spectrum of BRPS, emphasizing the importance of long-term monitoring and vigilance regarding potential complications, such as cardiac abnormalities, in BRPS patients.